Komparasi Mekanisme Penyelesaian Sengketa Pemilu di Beberapa Negara Penganut Paham Demokrasi Konstitusional - Bisariyadi Bisariyadi; Anna Triningsih; Meyrinda Rahmawaty H; Alia Harumdani W (Jurnal Konstitusi, 2012)
Every country in the world, moreover in every country which has implemented the way of life of democcratic and nation, presume that election is one of the important element as a marker of democracy of the country and also has a practical function of government political as a succession’s tool between the government parties and the oposition parties. In every democratic constitutional state, the election process has  a purpose to embody will of the people into pattern of power without violence.The election process will not only be assessed by sticking to the existing legal framework but the laws, codes of conduct of the election and its implementation needs to be tested and adjusted if it is in accordance with its primary purpose  or not without ignoring  the  rights  of  individuals  or  people.  In  the  process  of  the general election, the election process does not always run smoothly. Various obstacles in the implementation of good elections that occurred both during and previous election, is a  problem  that  certainly  would  have  widely  spread  impact if not immediately resolved. The existence of problems in the election related to dissatisfaction of decision of the election or criminal violations and administrative which can influence the result of election is commonly known by electoral disputes. In order the election dispute does not disturb the constitutional system or system of government of a country or region, it requires an electoral dispute resolution mechanisms that effective and can give a fair decision to the parties.The main problem is how the benchmark of an electoral dispute resolution mechanisms that are effective? Because, if traced further and reflect on democracies country in the world, not all democracies country, especially the democracies country which basing on the supremacy of the constitution, has the same electoral dispute resolution mechanisms between one country to another country. This is very important, because by knowing the measure or the benchmark of the effectiveness of an electoral dispute resolution mechanisms, we can consider to choose which electoral dispute resolution mechanisms that appropriate and give the fairness to the parties and society in general.